Mastering Adobe Captivate 2019 : build cutting edge professional SCORM compliant and interactive eLearning content with Adobe Captivate /: build cutting edge professional SCORM compliant and interactive eLearning content with Adobe Captivate. (2019) - Jaisingh, Pooja; Bruyndonckx, Damien
No abstract available